The Influence of the Implementation of the Emancipated Curriculum and Independent Teaching Platform on Teacher Competence at SMAN 21 Makassar - Hijar Semi; St. Syamsudduha; Muh Rapi (Journal of Pedagogi, 2025)
This study aims to determine; 1) whether there is a positive and significant influence of the implementation of the emancipated curriculum on teacher competence at SMAN 21 Makassar; 2) whether there is a positive and significant influence of the use of the independent teaching platform on teacher competence at SMAN 21 Makassar; and 3) whether there is a positive and significant influence together between the implementation of the emancipated curriculum and the independent teaching platform on teacher competence at SMAN 21 Makassar. The type of research used is quantitative ex post facto. The respondents in this study were teachers at SMAN 21 Makassar who were obtained based on the calculation of the Krejcie and Morgan table with a sample size of 66 people. The data collection method used a questionnaire instrument for the implementation of the emancipated curriculum, the independent teaching platform and teacher competence. The research data were analyzed using descriptive and inferential data analysis using simple linear regression analysis and multiple linear regression analysis. The results of this study indicate that; 1) there is an influence of the implementation of the emancipated curriculum on teacher competence at SMAN 21 Makassar of 6%; 2) there is an influence of the independent teaching platform on teacher competence at SMAN 21 Makassar of 6.1%; 3) There is a positive and significant influence between the implementation of the emancipated curriculum and the independent teaching platform together on teacher competence at SMAN 21 Makassar by 9.4%.